Engaging women’s groups to improve nutrition: Findings from an evaluation of the Jeevika multisectoral convergence pilot in Saharsa, Bihar - Gupta, Shivani; Kumar, Neha; Menon, Purnima; Pandey, Shinjini; Raghunathan, Kalyani (World Bank, 2019)
This report presents the endline findings of an impact evaluation of the JEEViKA Multisectoral Convergence pilot, designed as an effectiveness trial, in one district in Bihar, India. JEEViKA, a rural livelihoods project, supports self-help groups (SHGs) - savings and credit-based groups of about 15-20 women, mostly targeted toward those from poor households - with the aim of improving their livelihoods and enhancing household incomes. The JEEViKA Multisectoral Convergence (JEEViKA-MC) pilot went a step further, leveraging these SHGs to address the immediate and underlying determinants of undernutrition among women and children. The multisectoral convergence model, developed by the Bihar Rural Livelihoods Promotion Society with technical support from the World Bank, was piloted in 12 Gram Panchayats of Saharsa district in Bihar. Two complementary sets of interventions-health and nutrition behavior change communication (BCC) to improve women’s knowledge and household practices, and efforts to improve service access through convergence -were layered onto the existing core package of JEEViKA activities and were targeted to women who were members of the SHGs already formed by JEEViKA. Within this target population, households with young children, mothers of young children, and pregnant women were the primary focus of the JEEViKA-MC pilot.